PENERAPAN PERMAINAN BALOK ANGKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN ANAK KELOMPOK B DI TA AL KAUTSAR KOTA MALANG - Yuliatiningsih Yuliatiningsih; Khoirul Asfiyak; Yorita Febry Lismanda (UNISMA, 2019)
The problem faced is that the development of preliminary counting is quite lacking and in the learning process the teacher rarely uses instructional media so that the learning process does not attract the interest and attention of the child so this makes the child feel bored in attending classroom learning. To anticipate these problems, the researchers wanted to plan the learning process activities with the application of number beam games to improve the development of the beginning of the group B children in TA AL Kautsar, Malang City. The implementation of class action research is made in 2 cycles consisting of four stages, namely the planning stage, the implementation phase, the observation stage, and the reflection stage. Cycle I was carried out by obtaining 71% of research results or 17 from 24 children, so that from repeated research so that in the second cycle there was an increase reaching 91% or 22 of 24 children who achieved the expected indicators. So that from this activity class action research can be seen that the development of the counting of the beginning of the child has increased.